Outcomes of Emergency Transcatheter Aortic Valve Replacement. (3rd November 2019) - Huang, Hans; Kovach, Christopher P.; Bell, Sean; Reisman, Mark; Aldea, Gabriel; McCabe, James M.; Dvir, Danny; Don, Creighton
Abstract : Objective . To identify outcomes of patients undergoing emergency transcatheter aortic valve replacement (TAVR) and determine predictors of in-hospital mortality. Background . Emergency TAVR has emerged as a viable treatment strategy for patients with decompensated severe aortic stenosis and/or regurgitation; however, data on patients undergoing emergency TAVR are limited. Methods . All emergency TAVR procedures were identified from a single tertiary academic center between January 2015 and August 2018. Results . 31 patients underwent emergency TAVR due to cardiogenic shock (26 patients), electrical instability with incessant ventricular tachycardia (2 patients), severe refractory angina (2 patients), and decompensated heart failure with hypoxemic respiratory failure requiring mechanical ventilation (1 patient). Mechanical circulatory support (MCS) was used in 16 (51.6%). MCS initiation occurred immediately prior to TAVR in 10 patients and placed post-TAVR in 6 patients. 6 patients died before hospital discharge (in-hospital mortality 19.4%). 1-year and 2-year survival rates were 61.0% and 55.9%, respectively. Univariate predictors of in-hospital mortality were preprocedural pulmonary artery pulsatility index (PAPi) ≤1.8 (66.7% vs. 20.0%, p = 0.01 ), intraprocedural cardiopulmonary resuscitation (CPR) (83.3% vs 4.0%, p ≤ 0.001 ), acute kidney injury post-TAVR (80.0% vs. 4.2%, p ≤ 0.001 ), initiation of dialysis post-TAVR (60.0% vs. 4.2%, p ≤ 0.001 ), and MCS initiation post-TAVR (50.0% vs. 12.0%, p = 0.03 ). MCS initiation before TAVR was associated with improved survival compared with post-TAVR initiation. Conclusion . Emergency TAVR in extreme risk patients with acute decompensated heart failure or cardiogenic shock secondary to severe aortic valve disease is associated with high in-hospital mortality rates. Careful patient selection taking into account right heart function, assessed by PAPi, and early utilization of MCS may improve survival following emergency TAVR.